(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
The present qualitative study aimed to identify the educational practices adopted by foster families in the state of Rio Grande do Sul. 10 foster carers participated in this research, 05 men and 05 women qualified and working in foster care services in different municipalities in Rio Grande do Sul. From the thematic analysis of educators’ speeches, central dimensions were highlighted such as the organization of routine, the establishment of limits, the strengthening of emotional bonds and the promotion of socialization. The results showed that family care goes beyond social protection, becoming a training space that promotes the integral development of children in care. Educational practices reflect a model of temporary parenting, marked by challenges, adaptations and intense emotional investment.